Abnormal screens among nonmutation carriers in the High Risk Ontario Breast Screening Program. Issue 5 (7th February 2021) - Castelo, Matthew; Brown, Zachary; Schellenberg, Angela E.; Mills, Jane K.; Eisen, Andrea; Muradali, Derek; Grunfeld, Eva; Scheer, Adena S.
Abstract: Background: The Ontario Breast Screening Program was expanded in 2011 to offer annual MRI and mammography to women with high‐risk genetic mutations (e.g., BRCA1/2) and women with strong family histories and ≥25% estimated lifetime risk of breast cancer. Data to support high‐risk screening is less clear in the nonmutation carrier group, as MRI has lower specificity among this population. The potential unintended consequences may be considerable and need to be explored. We aimed to describe the frequency of abnormal screens and biopsies. Methods: Demographic surveys and chart review consent were sent to a sample of 441 individuals enrolled in a high‐risk screening program at two tertiary care hospitals in Toronto, Ontario. Retrospective cross‐sectional chart review was undertaken for clinicopathologic data. The frequencies of abnormal screens and biopsies were calculated. Results: One hundred sixty‐nine nonmutation carriers were included. The majority were white, employed, and highly educated. The median International Breast Cancer Intervention Study lifetime risk of breast cancer was 28.0% (range 24.5%–89.0%). 108 individuals (64%) experienced at least 1 abnormal screen and 13 (8%) had 3 or more over a median 3 years of screening (range 1–6 years). Of 55 biopsies, 3 (5.5%) were malignant. The cancer detection rate was 8.4/1000 screens (95% CI 3.2–22.4). Conclusions: An MRI‐based screening program for nonmutation carriers was effective at diagnosing breast cancer. However, this population experienced a high rate of abnormal screens and intervention. Further research is needed to improve the performance of MRI‐based screening in these women.